Comparison of the manual stimulation test and the nonstress test: A randomized controlled trial - Piyamongkol W. (2014)
Objective: To evaluate manual fetal stimulation (MST) through the maternal abdomen in comparison to standard nonstress test (NST) in terms of nonreactive rates and testing time. Material and Method: Five hundred and forty high-risk singleton pregnancies at 28 gestational weeks or more were assigned to have either NST or MST using blocked randomization (270 each). All fetal heart rate (FHR) tracings were analyzed blindly using standard NST criteria by one perinatologist. Results: The MST group provided a significantly higher reactive rate than that of the NST group, 98.9% and 84.4% respectively, p < 0.001. Mean testing time of the reactive results of the MST group was also significantly shorter than that of the NST group, 7.94 ± 6.27 min and 13.91 ± 9.58 min respectively, p < 0.001. Conclusion: This is the first randomized controlled trial (RCT) to demonstrate the distinctive benefit of the simple and less expensive MST. MST significantly reduces the time to reactivity and increases the frequency of reactivity when compared to NST alone.